A novel Ethernet based processing system for remote source harmonic detection - Mazin R. Khalil; Laith A. Mohammed; Omar N. Yousif (Universitas Ahmad Dahlan, 2023)
This work is carried out to objectively establish a new method to detect harmonics and measure the total harmonic distortion (THD) in a remote source, such as a high voltage transformer. The proposed approach utilized embedded design techniques to construct an embedded processor system with Ethernet intellectual property core to acquire data from a remote harmonics source. The designed system has several notable merits, namely, it is portable that can be applied in the work field, and it avoids workers from being subject to a hazard high voltage shock as well as its simplicity and high accuracy. The harmonics detection and analysis are achieved by inserting a microcontroller system near the high voltage transformer to acquire the necessary data and transmit it to a remote embedded processor system that is used to detect and analyze the harmonics. The microcontroller and the processor systems are connected by a wide-area network (WAN) through Ethernet and transmission control protocol/internet protocol (TCP/IP) protocols. The processor system is accommodated to perform 128 points fast Fourier transform for harmonics detection. Matlab simulations are used to validate the results. It is found that the results match very accurately the simulation results with an error of less than 0.02%.